Complications and outcomes of open posterior lumbar spinal fusion surgery in obese patients: a meta-analysis. (4th July 2022) - Xu, Yu-Zhu; Wang, Yun-Tao; Fan, Pan; Yin, Xiang-Jie; Liu, Hang; Jiang, Feng
Abstract: Objective: The aim of this study was to determine whether obesity affects the operation, complications and outcomes after open posterior lumbar spinal fusion surgery for the treatment of low back pain and leg pain. Methods: A meta-analysis of studies that compared the outcome of posterior lumbar spinal fusion in obese and non-obese patients. A total of 16 studies were included. Results: There was no difference in pain and functional outcomes. Posterior lumbar spinal fusion in obese patients resulted in a statistically significant increase in intra-operative blood loss (weighted mean difference 40.93, 95% confidence interval (CI) 15.97–65.90, n  = 243, and p =.001), longer duration of surgery (weighted mean difference −1.64, 95% CI −4.12 to 0.84, n  = 1460, and p =.19), more complications (odds ratio: 1.59, 95% CI 1.24–2.05, n  = 339, and p <.001) and extend length of stay (weighted mean difference 0.31, 95% CI 0.07–0.55, n  = 1408, and p =.01). Conclusions: Obese patients experience more blood loss, longer duration of surgery, more complications and extended length of stay, but their back and leg pain and functional outcomes are similar to non-obese patients. Based on these results, obesity is not a contraindication to open posterior lumbar spinal fusion surgery.